Internet of Things – Emergence of standards - Poikolainen, Janne (2012)
Poikolainen, Janne Internet of Things – Emergence of standards Jyväskylä: University of Jyväskylä, 2012, 34 p. Information System Science, Bachelor's Thesis Supervisor: Mazhelis, Oleksiy Internet of Things is a paradigm referring to the pervasive presence of networked things and objects that are able to interact and cooperate with each other. This paradigm also suggests that in the future these objects also produce large amounts of data to the internet and other network applications. Predictions say that the amount of data produced by things proceeds human produced data in the near future. These visions are grounded in the assumption that the advances in microelectronics, communications and information technology added with diminishing prices of these technologies will bring networking and cooperation capabilities to more and more every day things. This thesis reviews what the Internet of Things means as a phenomenon, how standards form in this field and challenges for Internet of Things standardization. Since IoT is a global phenomenon standardization plays a key role in the development of IoT. For this reason this thesis focuses to the standardization activities and not only to introducing technologies associated with IoT. First two chapters deal with the phenomenon and technology. But chapters three and four focus on challenges on IoT standardization and some of the IoT standards that already exist.